The Superiority Of Frodo Baggins Among Other Creatures In The Lord Of The Rings Movie - Ahmad Habibie (2008)
This study attempts to discuss the superiority produced by characters in The Lord of the Rings movie series. The characters have responsibility to escort the dark soul, the One Ring, to be destroyed in Mount Doom. The main concern of this study is to explore the society which is made by each race in the movie. The study specifies the research to analyze a major character, Frodo Baggins. His superiors embody him as a chosen one to be Ring Bearer. In analyzing the issue, the writer uses intrinsic theocy to examine the elements of literacy works which are characters and setting. By applying the theocy, the writer finds that there is uniqueness in Frodo's characterization, in terms of mastering the Controlling Ring, Sauron's Ring. From those findings, the writer sums up that only the power of sincerity could destroy the highest dark soul, the Ring of Sauron.